Gender Lens & Musician Lens On Male Netizen Comments Towards Indonesian Female Musicians On Instagram - Prihatiani, Khairunnisaa Damar; Afifah, Fidya Zahra; Zuhri , Hafizhah; Fairuzsalwa, Salsabila Mierszan; Nikita, Salsabila Nafa (KOMUNIKA, 2026)
This study explains how male netizens' comments respond to comments published on seven female musicians' Instagram accounts, framed by Objectification Theory, where women are often faced with a double standard between professionalism and femininity. Data collection was conducted on 106 Instagram comments, categorizing comments into two categories: Gender Lens (objectification, sexualization, and focus on personal life) and Music Lens (music appreciation and support). This study found that gender bias is still very dominant: 78.30% of comments contained objectification, 33.01% included sexualization, and 35.84% placed musicians as personal figures before professional ones. However, the digital space also shows a positive side thru appreciation for music quality (62.26%) and high audience support (93.39%). The research results indicate that there is still a high level of objectification, but it is also accompanied by a high level of audience support. Instagram, as a platform for appreciating music, can also be a place for expressing patriarchal comments. This research is expected to contribute to the study of Feminist Media Studies and affirm the importance of digital literacy and more gender-responsive platform policies.